2-D Modes Analysis of Micro-Ring Resonator: In case of chemical vapor sensing - Ramza, H. (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper describes 2-D modes analysis on the waveguide structure. Micro-Ring Resonator formation was simulated to able the chemical vapor detection by using COMSOL Multiphysics application. We present the simulation of mode analysis from a Micro-ring Resonator as sensing the chemical vapor. By implementing the device parameters. We have seen from the simulator that the optical mode is handled equally within the ring. Using the variation of effective refractive index, our simulator result of ring resonator generated the mode analysis in two-dimension perspective. We conclude that the ring resonator device has potential for generating the certain wavelength. Â© 2021 IEEE.